أهمية بعض الصفات الكمية في هجن من الذرة الصفراء (Zea mays L.) مستنبطة باستخدام الطريقةTester) (Line × - خوري, بولص; الأحمد, سمير; علي, ريم (Latakia University Journal -Biological Sciences Series, 2018)
This research was aimed to study grain yield, number of rows per ear, number of grains per row, angle of leaf, weight of hundred grains for thirty hybrids produced using line by tester method for ten inbred lines and three testers during 2015-2016 growing seasons at the Agricultural Research Center in Lattakia. the experiment was carried out by R.C.B.D design with three replications. Results indicated that: Mean squares of inbred lines, and hybrids were highly significant for all studied traits indicating the presence of genetic distance among parental lines. Most of the hybrids were significantly superior to AL-Bassel-1 hybrid. The grain yield was positively and significantly associated with number of rows per ear, number of grains per row, and weight of hundred grains. Grain yield was negatively and significantly associated with leaf angel. Grain yield improvement can be achieved through selection for number of rows per ear, number of grains per row, weight of hundred grains, and selection for acute angels أجري هذا البحث بهدف دراسة صفة الغلة الحبية (طن/هـ)، عدد الصفوف بالعرنوس (صف)، عدد الحبوب بالصف (حبة)، زاوية الورقة (درجة)، وزن المئة حبة (غ)، ومدى ارتباط هذه الصفات بصفة الغلة الحبية، لثلاثين هجيناً فرديّاً من الذرة الصفراء أنتجت باستخدام طريقة التهجين سلالة × مختبر بين عشر سلالات مربّاة داخليّاً وثلاث سلالات اختبارية خلال موسم 2015، وذلك في مركز البحوث الزراعية في اللاذقية. قيّمت الهجن الفرديّة في موسم 2016 حيث نفّذت التجربة بتصميم القطّاعات الكاملة العشوائيّة وبثلاثة مكررات وخلصت النتائج إلى ما يلي: أظهرت السلالات الأبوية، والهجن المستنبطة تبايناً عالي المعنوية لجميع الصفات المدروسة دلالة على التباعد الوراثي بين السلالات الأبوية. تفوقت معظم الهجن المستنبطة بشكل معنوي على هجين المقارنة الباسل-1 ارتبطت صفة الغلة الحبية ارتباطاً موجباً عالي المعنوية بكل من صفة عدد الصفوف بالعرنوس، عدد الحبوب بالصف، وزن المئة حبة. ارتبطت صفة الغلة الحبية ارتباطاً سلبياً عالي المعنوية بصفة زاوية الورقة. يمكن تحسين غلة محصول الذرة الصفراء بتطبيق الانتخاب لصفات عدد الصفوف بالعرنوس، عدد الحبوب بالصف، وزن المئة حبة، والانتخاب لصفة زاوية الورقة الحادة.